Mobile ECG monitoring for atrial fibrillation management: A literature review - Vincent Pearson (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Atrial fibrillation is the most prevalent arrhythmia associated with the risk of developing stroke and heart failure. Catheter ablation and electrical cardioversion are standard interventional procedures to treat atrial fibrillation. Patients are recommended to undertake regular heart rhythm assessment after the procedure due to the high recurrence rate of atrial fibrillation. Multiple mobile applications with high sensitivity and accuracy rates in rhythm analysis have been developed to support on-demand rhythm monitoring. This literature review aims to provide an overview of emerging evidence about the impact of mobile ECG monitoring on AF management. Keywords and index terms used in the search strategy include